Assessing for domestic violence in sexual health environments: a qualitative study. (4th August 2017) - Horwood, Jeremy; Morden, Andrew; Bailey, Jayne E; Pathak, Neha; Feder, Gene
Abstract : Objectives: Domestic violence and abuse (DVA) is a major clinical challenge and public health issue. Sexual health services are an important potential site of DVA intervention. The Assessing for Domestic Violence in Sexual Health Environments (ADViSE) intervention aimed to improve identification and management of DVA in sexual healthcare settings and is a modified version of the Identification and Referral to Improve Safety (IRIS) general practice programme. Our qualitative evaluation aimed to explore the experiences of staff participating in an IRIS ADViSE pilot. Methods: Interviews were conducted with 17 sexual health clinic staff and DVA advocate workers. Interviews were audio recorded, transcribed, anonymised and analysed thematically. Results: Staff prioritised enquiring about DVA and tailored their style of enquiry to the perceived characteristics of patients, current workload and individual clinical judgements. Responding to disclosures of abuse was divided between perceived low-risk cases (with quick onwards referral) and high-risk cases (requiring deployment of institution safeguarding procedures), which were viewed as time consuming and could create tensions with patients. Ongoing training and feedback, commissioner recognition, adequate service-level agreements and reimbursements are required to ensure sustainability and wider implementation of IRIS ADViSE. Conclusions: Challenges of delivering and sustaining IRIS ADViSE included the varied styles of enquiry, as well as tensions and additional time pressure arising from disclosure of abuse. These can be overcome by modifying initial training, providing regular updates and stronger recognition (and resources) at policy and commissioning levels.